Chronicle of the Oligocene succession (Kirkuk Group) in Duhok Governorate, Kurdistan Region, North Iraq - Karim, Kamal Haji; Hama, Briar Ahmad (Sulaimani Journal for Pure and Applied Sciences, 2019)
The previous studies referred to the Duhok area as a terrestrial uplift during Oligocene while the present study achieved completely different result by recording and mapping about 20-30 meters thick succession of the Oligocene Rocks (Kirkuk Group) for first time. The succession extends for about 20 kilometers inside the High Folded Zone and the previous basin boundary of Oligocene shifted to north for more than 50 kilometers. The succession consists of lagoonal limestone and changes in certain places, in the north, to patchy reef. Few beds of polymictic and limestone conglomerates intervened the succession in different levels. The Middle and Upper Oligocene index fossils are common, the most significant ones are Archias hensoni, Austrotrillina howchini, Praerhapydionina delicata, Peneroplis evolutus, Archias asmariensis, Archias kirkukensis and spirolina austrica. The main facies are coral and red algae bounstone, foraminifera and intraclast packstone to grainstone, pelecypod gastropod bioclast packstone to grainstone. The paleogeography setting (model) of the Oligocene is discussed in detail, compared with previous model and new model is drawn.
Keywords: Duhok stratigraphy; Oligocene succession; Oligocene paleogeography; Oligocene tectonics